Studi Literatur : Potensi Antikanker Ekstrak Kulit Manggis (Garcinia mangostana L.) - Najwa Adiva Faiza Setyawan; Vriezka Mierza (Jurnal Sehat Mandiri, 2026)
Cancer is a leading cause of death worldwide. Cancer therapy methods such as surgery, radiotherapy, and chemotherapy often cause serious side effects. Active compounds derived from natural sources are considered a promising alternative in the search for new anticancer agents because they are believed to have minimal adverse effects. This study aims to scientifically examine the anticancer potential of mangosteen peel extract. A systematic literature review was conducted using the PubMed database. The search was restricted to articles published between 2015 and 2025, and article selection followed predefined inclusion and exclusion criteria. The inclusion criteria consisted of original full-text research articles written in English that investigated mangosteen peel extract or xanthone compounds in relation to anticancer activity. Articles were excluded if they were not original studies, not full text, not written in English, published before 2015, or did not examine the anticancer activity of mangosteen peel. A total of 440 articles were identified, and 9 studies met the inclusion criteria. The results of the literature review show that mangosteen peel extract has demonstrated anticancer potential against cervical, ovarian, liver, lung, tongue, oral cavity, and glioma cancer cells. Conclusion: Mangosteen peel extract contains xanthones with strong anticancer potential via apoptosis induction, proliferation inhibition, and promising development as natural therapy.